DIAGNOSTIC PARENTING STYLE (IDEPS) INSTRUMENT TO IMPROVE SELF-ESTEEM IN THE YOUNGER GENERATION - Susanti, Maulida Rahma; Istiqomah, Dita Nurul; Salsabilah, Siti Nihar; Jannata, Taufan (Sentra Kekayaan Intelektual dan Inovasi Teknologi (INOTEK) Universitas Sains Al-Qur'an, 2024)
Currently, many young generations have mental problems caused by low self-esteem. Many factors can influence high and low self-esteem, including parenting patterns. However, the problem that occurs is that many parents do not know the parenting patterns they apply. This study aims to develop a Diagnostic Parenting Style Instrument (IDePS) that can diagnose the type of parenting pattern applied by parents, so that parents can know the type of parenting pattern they use and how it impacts their children's self-esteem. This study uses the Research and Development (R&D) method. The suitability of the measurement model as well as the validity test of the Diagnostic Parenting Style Instrument construct was analyzed using Confirmatory Factor Analysis (CFA). The results showed that the instrument developed used the IP Scale, which consisted of 30 questions. The instrument consists of two dimensions of parenting patterns, namely the responsive dimension and the demanding dimension. The Diagnostic Parenting Style Instrument (IDePS) has characteristics as an instrument that meets the requirements for use. This is indicated by the results of statistical testing using CFA, where the instrument has good model suitability. Overall, the Diagnostic Prescribing Style (IDePS) Instrument has good reliability with loading factors of 0.42, 0.32, 0.36, 0.48, 0.44, 0.33, 0.3, 0.34, 0.38, 0.35, 0.38, 0.31, 0.4, 0.3, 0.37, 0.38, 0.42, 0.45, 0.41, 0.38, 0.3, 0.52, 0.3, 0.34, 0.47, 0.56, 0.35. Diagnostic Instruments Parenting Style (IDePS) is also effective in diagnosing the type of parenting style applied by parents. Through this instrument, parents can evaluate the type of parenting style they apply to improve self-esteem in the younger generation in the future.